Poziom rozwoju społeczno-gospodarczego regionu śląskiego na tle województw Polski - analiza statystyczna - Hetmańska, Swietłana (The level of the social-economic growth of the Silesian region comparing to other voivodships of Poland - statistical analysis, 2005)
The regional social-economic growth research is the main subject of many papers. To provide regional politics correctly it is necessary to know the strengths and the weaknesses of the regions-voivodships. The aim of this article is to analyze the level of the social-economic growth of the Silesian region comparing to other voivodships of Poland. To measure the changes of level of growth three years were chosen - 1998 - the year right before administrative reform, and the years 2000 and 2001. The analysis deals with the level of economic growth, level of life and quality of life.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 250-260